(untitled) (Indian Journal of Animal Production and Management, 2024)
Livestock sector, especially cattle, is a large contributor to the national economy and a vital nutrition source for millions of people in Bangladesh. Majority of the rural farmers are involved in the homestead cattle rearing along with their main crop cultivation and many of them are using commercial cattle rearing as their main occupation. While rearing cattle, it is usual for them to encounter different cattle diseases and they, to their best of the abilities, look for information to manage those diseases. This study, thus, was undertaken to explore the information search and seeking behavior of the cattle farmers for cattle disease management. The study was based on Wilson’s nested model of information behavior. It was carried out in Madargonj and Sharishabari sub-district of Jamalpur district of Bangladesh. One hundred farmers were interviewed using a semi-structured questionnaire. Appropriate scales were used to measure the concerned variables. Descriptive analysis was done to see the outcome of the study. It was observed that farmers faced low to moderate disease infestation in their cattle and worm infestation being the most frequent one. They, besides, search for information from less to a moderate degree. Farmers tend to approach local sources like experienced farmers, neighbours and friends, large local farmers etc. for information. They seek other information sources only when something is beyond the capabilities of local sources like vaccination or medicine prescription for disease management. The lack of field-level livestock extension worker seems to be one of the major factors that break the information flow between farmers and Government agencies. The lack of Government campaigns related to livestock extension is also contributing for not influencing farmers to look for specialized and professional information sources. Government agencies and other relevant organizations working in livestock extension field should take initiatives to reach to the farmers and spread the importance to look for diversified sources to have professional and authentic cattle health-related information. Besides, it seems to be a timely need to recruit more field-level livestock extension workers in Bangladesh so that farmers can easily access better professional opinion on cattle disease management.